Reproductive Biology of the Blue Swimming Crab Portunus pelagicus (Brachyura: Portunidae) in East Lampung Waters, Indonesia: Fecundity and Reproductive Potential - Zairion,; Yusli Wardiatno,; Mennofatria Boer, (Tropical Life Sciences Research, 2015)
The blue swimming crab Portunus pelagicus is an important catch species for many coastal villages along the Java Sea coastline, but little is known regarding its reproductive biology or stock status. We examined the batch fecundity of female crabs that were collected monthly at landing sites from June 2011 to May 2012, calculated the relationships with body size, egg mass and month of the year, and determined the size at which females became potentially reproductive in the population inhabiting East Lampung waters (western Java Sea). Fecundity values ranged from 229,468 to 2,236,355 (mean = 926,638±30,975 [±SE]). The fecundity was positively and linearly correlated with carapace width (CW), but the relationships with body weight and egg mass were best described by logarithmic regression. A peaked, temporally cyclical pattern in fecundity was observed, with a peak period that was significantly different (F = 226.36; df = 22, p<0.05) from March to May 2012. Reproductive females were within the 111.0–155.9 mm CW size range; significantly higher reproductive potentials (F = 14.59; df = 30, p<0.05) were found in females within the 126.0?130.9 mm CW size group. The current minimum legal size (MLS = 100 mm CW) is not an appropriate limit reference point, and a precautionary approach is needed for a sustainable harvesting strategy. Resetting the MLS to 115 mm CW would potentially provide adequate protection for spawning females and increase total egg production, thereby maintaining population productivity and enhancing resilience in the face of current fishing pressures. Ketam renjong Portunus pelagicus merupakan spesies penting untuk banyak perkampungan persisiran pantai di perairan Laut Jawa, tetapi status pembiakan dan stok spesies tersebut kurang diketahui. Kami telah mengkaji fekunditi ketam betina yang telah dikutip setiap bulan dari tapak pendaratan dari Jun 2011 hingga Mei 2012, telah mengira perhubungan dengan saiz badan, jisim telur dan bulan dalam tahun, dan telah mengetahui saiz betina yang berpotensi untuk membiak dalam populasi yang menghuni di perairan Timur Lampung (barat Laut Jawa). Nilai-nilai fekunditi ialah daripada 229,468 hingga 2,236,355 (min = 926,638±30,975 [±SE]). Nilai ini positif dan berkorelasi secara linear dengan lebar karapas (CW), tetapi perhubungan dengan berat badan (BW) dan jisim telur diterangkan terbaik menggunakan regresi logaritma. Satu corak puncak, yang berkitaran sementara dalam fekunditi dilihat, dengan tempoh puncak yang berbeza secara signifikan (F = 226.36; df = 22, p<0.05) daripada Mac hingga Mei 2012. Betina yang boleh membiak berada dalam julat CW sebanyak 111.0–155.9 mm; potensi pembiakan yang tinggi secara signifikan (F = 14.59; df = 30, p<0.05) dijumpai dalam kumpulan betina dengan CW sebanyak 126.0?130.9 mm. Saiz minimum sah (MLS = 100 mm CW) masa kini tidak sesuai sebagai titik rujukan limitasi, dan satu langkah berjaga-jaga diperlukan untuk strategi penangkapan yang lestari. Pengesetan semula MLS kepada CW 115 mm berpotensi untuk memberi perlindungan secukupnya kepada betina yang membiak, dan meningkatkan produksi total telur, maka mengekalkan produktiviti populasi dan meningkatkan kebingkasan dalam pada menghadapi tekanan perikanan masa kini.